1999
DOI: 10.1046/j.1365-2222.1999.00479.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hay fever and allergic sensitization in farmer's children and their peers living in the same rural community

Abstract: Factors directly or indirectly related to farming as parental occupation decrease the risk of children becoming atopic and developing symptoms of allergic rhinitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
356
6
21

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 590 publications
(418 citation statements)
references
References 24 publications
32
356
6
21
Order By: Relevance
“…Only one farm child was allergic at 3 years of age, as compared with ten in the non-farm group. The protective effect of growing up on a small, family-owned dairy farm is in line with previous studies [2,4,36]. Recent randomized trials point to postponement of introduction of solid foods as a strong risk factor for development of food allergy [15,16] and several observational studies have pointed to delayed introduction of fish as predictive of high risk of becoming allergic [2229].…”
Section: Discussionsupporting
confidence: 82%
“…Only one farm child was allergic at 3 years of age, as compared with ten in the non-farm group. The protective effect of growing up on a small, family-owned dairy farm is in line with previous studies [2,4,36]. Recent randomized trials point to postponement of introduction of solid foods as a strong risk factor for development of food allergy [15,16] and several observational studies have pointed to delayed introduction of fish as predictive of high risk of becoming allergic [2229].…”
Section: Discussionsupporting
confidence: 82%
“…Swiss school children showed to have atopy, measured by radioallergosorbent test, and symptoms of hay fever significantly less frequently than children from the same area who have not been growing up on a farm (114). This inverse association between exposure to farm/country environment in childhood and the subsequent development of atopic disorders has been confirmed by further studies in Germany (115), Austria (116,117), Finland (118), Denmark (119), Canada (120) and France (121) There is also some evidence to suggest that exposure to country living also in later childhood or even in adulthood 'ever living in the country' may confer protection against asthma and atopy implicating that immunomodulation may not be restricted to exposure in the first years of the life only (121).…”
Section: Exposure To Farm/country Environment and Petsmentioning
confidence: 90%
“…It has become evident that something is lacking from our affluent societies that has the capacity to protect against the development of atopic (and autoimmune) diseases (102) Growing up on a farm may confer protection against atopy (114) Exposure to pets (cats and dogs) in early life may confer protection against atopy (123) 2000 Exposure to LPS in home dust may confer protection against atopy (93) Exposure to helminths may confer protection Current hygiene hypothesis; against the expression of atopic disease (134) Orofecal and helminth infections, 2001…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies of Swiss, Bavarian, and Austrian children have shown that the prevalence of symptoms of allergic rhinitis and of allergen-speci®c IgE antibodies is much lower among the offspring of farmers than among other children in these areas (57). In a recent Swedish study (58), the prevalence of atopy in children from anthroposophic families was found to be lower than in children from other families, a ®nding which led the authors to the conclusion that lifestyle factors associated with anthroposophy may lessen the risk of atopy in childhood.…”
Section: Lifestyle and The Development Of Atopic Diseasementioning
confidence: 99%